Identification of novel mutations and risk assessment of Han Chinese patients with autosomal dominant polycystic kidney disease. Issue 5 (17th April 2019) - Zhang, Mingchao; Liu, Shuaimei; Xia, Xinyi; Cui, Yingxia; Li, Xiaojun
ABSTRACT: Aim: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disease in humans and is caused by mutations in the PKD1 or PKD2 gene. ADPKD is heterogeneous with regard to locus and allele heterogeneity and phenotypic variability. Methods: Using targeted capture associated with next generation sequencing (NGS), we performed a mutational analysis of Han Chinese patients with ADPKD from 62 unrelated families. Multivariate Cox proportional hazard modelling of their different clinical characteristics and mutation classes was performed. Results: The detection rate for a PKD1 and PKD2 mutation in the Chinese ADPKD patients was 95.2% (59/62). We identified pathogenic mutations in 64.4% (38/59) of patients, including 32 PKD1 mutations (15 nonsense mutations, 15 frameshift mutation, one splice mutation, and one large deletion) and six PKD2 mutations (three nonsense mutations and three frameshift mutations). Of the pathogenic variants we identified, 50% (19/38) were novel variants and 50% (19/38) were known variants. Patients with PKD2 mutations had milder and indistinguishable phenotypes. Significant phenotypic differences were observed among the various types of PKD1 mutations. Conclusion: Our results show that targeted capture associated with next‐generation sequencing is an effective strategy for genetically testing ADPKD patients. This mutation analysis of ADPKD in Han Chinese extends our understanding of the genetic diversity of different ethnic groups, enriches the mutation database, and contributes to the genetic counselling of ADPKD patients. Summary at a Glance: This paper adds to the literature of variants in PKD1 and PKD2 that are associated with clinical polycystic kidney disease in a previously under reported population.